The emerging role of lysine succinylation in ovarian aging - Meiling Le; Jia Li; Dalei Zhang; Yuan Yuan; Chong Zhou; Jinxia He; Jian Huang; Liaoliao Hu; Tao Luo; Liping Zheng (BMC, 2023)
Abstract Background Ovarian aging is a process of decline in its reserve leading to ovary dysfunction and even reduced health quality in offspring. However, aging-related molecular pathways in the ovary remain obscure. Lysine succinylation (Ksuc), a newly post-translational modification (PTM), has been found to be broadly conserved in both eukaryotic and prokaryotic cells, and associated with multiple pathophysiological processes. There are no relevant reports revealing a link between the molecular mechanisms of ovarian aging and Ksuc. Methods The level of Ksuc in ovaries of aged and premature ovarian insufficiency (POI) mice were detected by immunoblotting and immunohistochemical. To further explore the role of Ksuc in ovarian aging, using in vitro mouse ovary tissue culture and an in vivo mouse model with changed Ksuc level. Results Increased Ksuc in ovaries of aged and POI mice and distribution of Ksuc in various types of mice ovarian cells and the high level of Ksuc in granulosa cells (GCs) were revealed. Histological assessments and hormone levels analyses showed that the high Ksuc level down-regulated the ovarian index and the anti-Müllerian hormone (AMH) and estrogen levels, and increased follicular atresia. Moreover, in the high Ksuc groups, the terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) intensities and the expression of Cleaved-caspase-3 increased and the expression of B-cell lymphoma-2 (Bcl-2) decreased together with positively-expressed P21, an aging-related marker. These results suggest that ovarian aging is likely associated with alteration in Ksuc. Conclusion The present study has identified Ksuc in mouse ovary and found that high Ksuc level most likely contributes to ovarian aging which is expected further investigation to provide new information for delaying physiological ovarian aging and treating pathological ovarian aging.